Neurohumoral Cardiac Regulation: Optogenetics Gets Into the Groove - Scalco, Arianna; Moro, Nicola; Mongillo, Marco; Zaglia, Tania (Frontiers in Physiology, 2021)
The cardiac autonomic nervous system is the main modulator of heart function, adapting contraction force and rate to the continuous variations of intrinsic and extrinsic environmental conditions. While the parasympathetic branch dominates during rest-and-digest, sympathetic neuron activation ensures the rapid, efficient and repeatable increase of heart performance, e.g. during the ‘fight-or-flight response’. Although the key role of the nervous system in cardiac homeostasis was evident to the eyes of physiologists and cardiologists, the degree of cardiac innervation and the complexity of its circuits has remained underestimated for too long. In addition, the mechanisms allowing elevated efficiency and precision of neurogenic control of heart function have somehow lingered in the dark. This can be ascribed to the absence of methods adequate to study complex cardiac electric circuits in the unceasingly moving heart. An increasing number of studies adds to the scenario the evidence of an intracardiac neuron system, which, together with the autonomic components, define a little brain inside the heart, in fervent dialogue with the central nervous system. The advent of optogenetics, allowing control the activity of excitable cells with cell specificity, spatial selectivity and temporal resolution, has allowed to shed light on basic neuro-cardiology. This review describes how optogenetics, which has extensively been used to interrogate the circuits of the central nervous system, has been applied to untangle the knots of heart innervation, unveiling the cellular mechanisms of neurogenic control of heart function, in physiology and pathology, as well as those participating to brain-heart communication, back and forth. We discuss existing literature, providing a comprehensive view of the advancement in the understanding of the mechanisms of neurogenic heart control. In addition, we weigh the limits and potential of optogenetics in basic and applied research in neuro-cardiology.